The Effect of Product Quality, Brand Image, and Customer Satisfaction On Customer Loyalty (As Study On Ultra Milk Consumers In Jakarta) - Rena Eva Nurisma; Zulvia Khalid (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2024)
In today's increasingly competitive business environment, building and maintaining customer loyalty has become a key determining factor in an organization's success and profitability. Customer loyalty generates recurring revenue through repeat purchases and serves as a brand advocate, driving organic growth by attracting new customers. However, cultivating customer loyalty requires a strategic and holistic approach, which includes product quality, brand image, and customer satisfaction. This research empirically explores the impact of product quality characteristics, brand image, and customer satisfaction on Ultra Milk customer loyalty in the Jakarta area. This study uses a quantitative approach to determine the causal relationship between these factors. The data was collected by distributing questionnaires to 100 active Ultra Milk consumers in Jakarta. SPSS 29 software is used for data analysis, specifically multiple linear regression. The findings of this study aim to contribute to a theoretical understanding of the factors that affect consumer loyalty in the dairy industry. Practically, the findings of this study are expected to be the foundation for Ultra Milk companies to develop more effective marketing strategies to increase and maintain customer loyalty. The recommendations given will focus mainly on statistically significant variables in influencing customer loyalty.